Tables for the hydraulic design of pipes, sewers and channels - Barr,D.I.H (Thomas Telford, 1994)
This is the second of the two volumes forming the 6th edition of the Wallingford Tables. Both volumes are free-standing in use with this volume providing an alternative solution system for the Colebrook-White equation.